2014
DOI: 10.1080/10942912.2013.787626
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoEvaluation of Potential DPP-III Inhibitor Precursors from Dietary Proteins

Abstract: Dipeptidyl peptidase-III is an important enkephalin degrading enzyme and its inhibitors are expected to be promising in pain management. Some of its inhibitors showed an antinociceptive potential. The present study investigated the evaluation of dietary proteins as potential precursors of dipeptidyl peptidase-III inhibitors by measuring occurrence frequency of dipeptidyl peptidase-III inhibitory peptides. In silico analysis of 69 proteins from 17 food commodities revealed 2659 dipeptidyl peptidase-III inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These opioid peptides regulate diverse physiological functions such as signal transduction, gastrointestinal motility, immune and endocrine functions, and mostly pain modulation. Dipeptides with aromatic residues such as YY, YF, and containing large aliphatic or basic amino acids have been described as potent inhibitors (Khaket et al 2015). Few studies have identified DPP III inhibitory peptides from meat proteins, however, hemoglobin could present a high potential as source of such bioactive peptides (Khaket et al 2015).…”
Section: Bioactivity Of Dipeptides and Tripeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…These opioid peptides regulate diverse physiological functions such as signal transduction, gastrointestinal motility, immune and endocrine functions, and mostly pain modulation. Dipeptides with aromatic residues such as YY, YF, and containing large aliphatic or basic amino acids have been described as potent inhibitors (Khaket et al 2015). Few studies have identified DPP III inhibitory peptides from meat proteins, however, hemoglobin could present a high potential as source of such bioactive peptides (Khaket et al 2015).…”
Section: Bioactivity Of Dipeptides and Tripeptidesmentioning
confidence: 99%
“…Dipeptides with aromatic residues such as YY, YF, and containing large aliphatic or basic amino acids have been described as potent inhibitors (Khaket et al 2015). Few studies have identified DPP III inhibitory peptides from meat proteins, however, hemoglobin could present a high potential as source of such bioactive peptides (Khaket et al 2015). In dry-cured hams, creatine kinase-derived dipeptides such as HK, HP, and LA would show DPP III inhibitory activity according to the BIOPEP database ( Table 3).…”
Section: Bioactivity Of Dipeptides and Tripeptidesmentioning
confidence: 99%
“…According to the report by Khaket et al [ 53 ], the β-subunit of chicken hemoglobin and annexin A5 showed a high inhibitory potential for DPP-III in in silico studies. However, as noted by Galleo et al [ 16 ], only a few studies identified peptides that inhibit DPP-III from meat proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This study was correlated with an earlier investigation, which was determined the dipeptidyl peptidase IV inhibitory activity of protein hydrolysates from tropical banded cricket 27 , salmon skin gelatin hydrolysates 50 , and quinoa protein hydrolysates 51 . This investigation is not surprising task since most peptides are identified as di-or tri-peptides and described to have dipeptidyl peptidase IV inhibitory activity 52,53 .…”
Section: Discussionmentioning
confidence: 97%